Institute of Metals Division - Ignition Temperatures of Magnesium and Magnesium Alloys - W. Martin Fassell; Leonard B. Gulbransen; John R. Lewis; J. Hugh Hamilton (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1952)
A simple reproducible method was developed for determining the ignition temperatures of magnesium and magnesium alloys and by this method magnesium and over 100 magnesium alloys were measured. The ignition temperature of magnesium was determined in O2-SO2, O2-N2 mixtures and in O2 from 0.166 to 10 atm pressure. The ignition temperature of magnesium is generally lowered by alloying and increased by an increase in oxygen pressure. WITH the expanded use of magnesium alloys in industry, ignition temperatures are of considerable importance, especially in heat treating and for service at elevated temperatures. Magnesium alloys exhibit a relatively slow linear oxidation rate up to temperatures near the melting point.' At some critical temperature the rate of oxidation becomes extremely rapid. This high rate of oxidation is accompanied by the emission of light and additional characteristics suggesting a flame. The literature concerning the ignition temperatures of magnesium and magnesium alloys is relatively incomplete and the values reported by various authors are not in agreement. The most probable reasons for this are: 1—The absence of a suitable definition of ignition, and 2—the need of a standardized method of determining the ignition temperatures of inflammable metals and alloys. The exact date of the discovery of the fact that magnesium will ignite and burn is unknown. It is likely that H. Davey encountered this property of the metal during its preparation in 1808. The first reference in the literature specifically on ignition of magnesium is by Lenze, Metz, and Rubens.' They investigated the inflammability of certain magnesium alloys. Brown3-' reported that magnesium ribbon will ignite in air at 507 °C by what was called the rising temperature method. Hartman, Nagy, and Brown" reported that magnesium powder ignites from 475" to 560°C depending on particle size. According to Guise, Mars, and Wilson prolonged heating in air at 427°C of common casting magnesium alloy causes it to ignite. Samples of magnesium alloys were placed directly in the flame of a torch by Carapella and Shaw.' These investigators obtained some evidence of melting prior to ignition. For commercial magnesium, they reported an ignition temperature of 650°C. Their values varied from 450" to 800°C for magnesium alloys. Willmore and Peterson" studied the effect of air velocity, humidity, rate of heating, and foreign metal contact on the ignition temperature of magnesium. They conclude that melting is not a prerequisite for ignition and that the conditions which influence ignition are complex and difficult to analyze. The only quantitative theoretical treatment of the ignition temperatures of magnesium and magnesium